Efficient cast iron inoculant containing rare earth elements

By constructing a multi-synergy and synergistic incubation system of scandium-ytterbium-subterium-terbium rare earth elements, the problem of poor performance of traditional cast iron incubator in high temperature environments is solved, and the high-temperature performance and service stability of cast iron are significantly improved, and the coordinated improvement of strength and toughness is achieved.

CN119859773AActive Publication Date: 2025-04-22CHENGDU HONGYUAN FOUNDING MATERIAL CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202510346235.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The existing cast iron inoculant does not perform well in high temperature, high pressure and high corrosion environments, and scandium-ytterbium-lutter-terbium rare earth elements have high activity and easy oxidation during application, making it difficult to meet the performance requirements of high-strength, tough and lightweight cast iron products.

Method used

Scandium-ytterbium-letterbium-terbium rare earth elements are used to build a multi-synergy and synergistic fertilization system. By selecting appropriate auxiliary elements and carrier elements, a microform of the "core-shell" structure is formed, and the release rate and nucleation efficiency of rare earth elements are optimized.

Benefits of technology

The tissue quality and comprehensive performance of cast iron are significantly improved, especially in high-temperature performance and service stability. The tensile strength is improved by about 50%, the hardness is improved by about 38%, the high-temperature strength retention rate reaches 64%, and the effective time window for fertilization treatment is significantly extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of cast iron alloys, in particular to an efficient cast iron inoculant containing rare earth elements. The nucleating agent comprises the following components in percentage by weight: 0.5 to 2.0 percent of scandium, 0.3 to 1.5 percent of ytterbium, 0.1 to 0.8 percent of lutetium and 0.2 to 1.0 percent of terbium; the raw materials comprise 30 to 45 percent of silicon, 0.5 to 2.5 percent of calcium, 0.2 to 1.0 percent of molybdenum, 0.1 to 0.8 percent of strontium and 0.1 to 0.5 percent of zirconium; 0.5-2.0% of aluminum and the balance of iron. Through the synergistic effect of four rare earth elements including scandium, ytterbium, lutetium and terbium in a certain proportion, the technical obstacles that the rare earth elements are high in activity, prone to oxidation and high in cost are overcome, and the comprehensive performance of the cast iron is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cast iron alloys, in particular to a high-efficiency cast iron inoculant containing rare earth elements. Background Art

[0002] As an indispensable basic material in the modern industrial system, cast iron materials are widely used in the fields of automotive parts, heavy machinery, energy equipment, aerospace, etc. With the advancement of science and technology and the continuous upgrading of industrial needs, the requirements for the performance of cast iron materials are increasing, especially the service performance in harsh environments such as high temperature, high pressure, and high corrosion. Inoculation treatment, as a key process to control the microstructure and optimize the performance of cast iron, has always been a hot topic in the casting field. The core of inoculation treatment is to add specific elements to the molten iron to provide a heterogeneous nucleation core during the solidification process, promote graphitization, and refine the structure, thereby improving the comprehensive performance of cast iron.

[0003] Traditional cast iron inoculants mainly include silicon-based inoculants (such as ferrosilicon, calcium silicon, etc.) and light rare earth-based inoculants (mainly containing cerium, lanthanum, etc.). These inoculants have been widely used in industrial production, but at the same time they have obvious limitations: the inoculation effect is easy to decline, especially when the molten iron is overheated or the insulation time is prolonged; the inoculation effect is sensitive to the composition and state of the molten iron, and it is difficult to achieve universality; the inoculation effect on special grades of cast iron is limited; some inoculants will introduce inclusions during use, which will affect the purity of the cast iron. More importantly, as cast iron products develop towards high strength, toughness and lightweight, traditional inoculants can no longer meet the increasingly high performance requirements.

[0004] In recent years, rare earth elements have shown great application potential in the field of materials science due to their unique electronic structure and physical and chemical properties. However, current industrial applications are mainly concentrated on light rare earth elements (such as cerium and lanthanum), while scandium-ytterbium-lutetium-terbium rare earth elements are not fully utilized due to their scarcity, high cost and difficulty in processing. With the advancement of rare earth extraction and separation technology, some scandium-ytterbium-lutetium-terbium rare earth elements that were neglected in the past are showing unique application value.

[0005] There are no reports in the prior art on the systematic use of scandium-ytterbium-lutetium-terbium rare earth elements to construct an efficient inoculation system, nor are there any in-depth studies on the synergistic mechanism of these rare earth elements. There is even less effective solutions to the problems of high activity and easy oxidation of scandium-ytterbium-lutetium-terbium rare earth elements during their application. Summary of the invention

[0006] The purpose of the present invention is to provide a high-efficiency cast iron inoculant containing rare earth elements, which can significantly improve the organizational quality and comprehensive performance of cast iron, especially high-temperature performance and service stability, by systematically utilizing the unique physical and chemical properties of scandium-ytterbium-lutetium-terbium rare earth elements to construct a multi-element synergistic inoculation system, while solving the technical obstacles in the application of scandium-ytterbium-lutetium-terbium rare earth elements.

[0007] The scandium-ytterbium-lutetium-terbium rare earth elements selected in the present invention include scandium (Sc), ytterbium (Yb), lutetium (Lu) and terbium (Tb).

[0008] Scandium, as a transition metal element, has the characteristics of small atomic radius, high ionization energy and strong oxygen affinity. Its high melting point compound can serve as a graphite nucleation substrate and help stabilize the inoculation effect; ytterbium, as a heavy rare earth element, has +2 / +3 valence variability, which can affect the redox environment in the molten iron under different temperature conditions; lutetium, as the heaviest rare earth element, may affect the uniformity of the casting structure through its compounds; terbium mainly affects the graphite nucleation environment through its chemical properties. These elements can work synergistically in cast iron inoculation and are expected to improve the structure and performance of cast iron.

[0009] Specifically, the present invention adopts the following technical solutions:

[0010] A high-efficiency cast iron inoculant containing rare earth elements, comprising the following components by weight percentage:

[0011] Scandium-ytterbium-lutetium-terbium rare earth elements: scandium (Sc) 0.5-2.0%, ytterbium (Yb) 0.3-1.5%, lutetium (Lu) 0.1-0.8%, terbium (Tb) 0.2-1.0%;

[0012] Auxiliary elements: silicon (Si) 30-45%, calcium (Ca) 0.5-2.5%, molybdenum (Mo) 0.2-1.0%, strontium (Sr) 0.1-0.8%, zirconium (Zr) 0.1-0.5%;

[0013] Carrier elements: aluminum (Al) 0.5-2.0%, the balance is iron (Fe).

[0014] The total content of the scandium-ytterbium-lutetium-terbium rare earth elements is 1.1-5.3%, preferably 1.5-3.5%.

[0015] The weight ratio of the four rare earth elements scandium, ytterbium, lutetium and terbium is 3:2:1:1.5.

[0016] Beneficial effects of the present invention:

[0017] Compared with traditional ferrosilicon inoculants and conventional rare earth inoculants, the inoculant of the present invention shows significant advantages in improving the mechanical properties of gray cast iron. The tensile strength is increased by about 50%, the hardness is increased by about 38%, and the elongation at break and impact toughness are also significantly improved, achieving a synergistic improvement in strength and toughness.

[0018] The inoculant of the present invention has excellent high-temperature performance, and its strength retention rate at a high temperature of 500°C reaches 64%, which is much higher than the 40-50% of the traditional inoculant, thereby greatly improving the service capacity of cast iron parts in high-temperature environments.

[0019] The inoculant of the present invention exhibits excellent anti-fading performance. After 60 minutes of heat preservation, the decay rate of the inoculation effect is only 7.6%, while the decay rate of the traditional inoculant is 30-40%, which significantly extends the effective time window of the inoculation treatment.

[0020] The inoculant of the invention has a significant effect of refining and homogenizing the cast iron structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 (a) is a comparison chart of the proportion of type A graphite in the embodiment group, Figure 1 (b) is a graphite size comparison diagram of the embodiment group, Figure 1 (c) is a graph comparing the amount of graphite in the embodiment group. Figure 1 (d) is a comparison chart of the A-type graphite ratio of the comparative group. Figure 1 (e) is a graphite size comparison diagram of the comparative example group. Figure 1 (f) is a graph showing the amount of graphite in the comparative example group;

[0022] Figure 2 (a) is the relationship between the proportion of type A graphite and the amount of addition. Figure 2 (b) is the relationship between graphite size and addition amount. Figure 2 (c) is the relationship between the amount of graphite and the amount added. Figure 2 (d) is the relationship between graphite distribution uniformity and addition amount;

[0023] Figure 3 (a) is a comparison chart of pearlite and ferrite content. Figure 3 (b) is a comparison chart of grain size. Figure 3 (c) is the relationship between pearlite content and mechanical properties (tensile strength and hardness). Figure 3 (d) is the relationship between grain size and impact toughness;

[0024] Figure 4 (a) is a comparison chart of the tensile strength of the embodiment group, Figure 4 (b) is a comparison chart of the tensile strength of the comparative group. Figure 4 (c) is the high temperature strength characteristic diagram, Figure 4 (d) is the relationship between hardness and impact toughness;

[0025] Figure 5 (a) is the high temperature strength retention rate diagram of the embodiment group, Figure 5 (b) is the high temperature strength retention rate diagram of the comparative group;

[0026] Figure 6 is a graph showing the improvement of high temperature strength retention rate relative to Comparative Example 1;

[0027] Figure 7 (a) is the relationship curve between the addition amount and the tensile strength. Figure 7 (b) is a graph showing the relationship between the growth rate of tensile strength and the amount of addition;

[0028] Figure 8 (a) is the relationship curve between tensile strength and holding time. Figure 8 (b) is the relationship curve between the proportion of type A graphite and the holding time. Figure 8 (c) is a graph showing the relationship between the decay rate and the holding time (example). Figure 8 (d) is a graph showing the relationship between decay rate and holding time (comparative example);

[0029] Fig. 9 (a) is the relationship between tensile strength and overheating temperature. Fig. 9 (b) is the relationship between the proportion of type A graphite and the overheating temperature. Fig. 9 (c) is the relationship between strength retention rate and overheating temperature;

[0030] Fig.10 (a) is the relationship curve between crack density and thermal cycle number. Fig.10 (b) is the curve of maximum crack depth and thermal cycle number. Fig.10 (c) is a graph of grain size and crack growth rate. Fig.10 (d) is a graph showing the improvement in thermal fatigue resistance;

[0031] Fig.11 (a) is the mass loss diagram under different wear conditions, Fig.11 (b) is the relative wear resistance diagram under different conditions. Fig.11 (c) is the relationship between hardness and wear resistance. Fig.11 (d) is the relationship between graphite size and wear resistance;

[0032] Fig.12 (a) is a graph showing the ratio of type A graphite and the amount of addition of a single element. Fig.12 (b) is the synergistic effect curve of combined rare earth elements. Fig.12 (c) is the combined bar graph of nucleation particle characteristics. Fig.12(d) is a bar graph of physicochemical properties;

[0033] Fig.13 This is a comparison chart of nucleation efficiency coefficients of different rare earth combinations;

[0034] Fig.14 This is the relationship diagram between supercooling degree and rare earth combination for different rare earth combinations. DETAILED DESCRIPTION

[0035] The composition of the inoculant is selected as follows.

[0036] Active element system selection:

[0037] The active element system is composed of four rare earth elements, scandium (Sc), ytterbium (Yb), lutetium (Lu) and terbium (Tb), which are the core functional part of the inoculant. Based on a large number of preliminary experimental results and theoretical calculations, the optimal ratio range of these four elements was determined, namely Sc: Yb: Lu: Tb = 3: 2: 1: 1.5.

[0038] Scandium (Sc) content is 0.5-2.0%, which acts as the main nucleation promoter to form high melting point compounds as heterogeneous nucleation cores;

[0039] The ytterbium (Yb) content is 0.3-1.5%, which acts as a valence control element to dynamically adjust the redox environment of the molten iron;

[0040] The content of Lu is 0.1-0.8%, which acts as a grain boundary control element to improve the matrix strength and thermal fatigue resistance;

[0041] The terbium (Tb) content is 0.2-1.0%, which serves as a magnetic regulation and multivalence regulation element to promote uniform nucleation.

[0042] The total content of the four rare earth elements is controlled within the range of 1.1-5.3%, preferably within the range of 1.5-3.5%, which ensures sufficient activity while taking into account economic efficiency. It is worth noting that there are complex interactions between the four elements, and changes in the content of any element will affect the optimal content of other elements, forming a complex multivariable optimization problem.

[0043] Auxiliary element system selection:

[0044] In order to enhance the effect of scandium-ytterbium-lutetium-terbium rare earth elements, while considering the economy and process practicality, the present invention selects the following auxiliary element system:

[0045] Silicon (Si) content is 30-45%, which is a traditional inoculating element that promotes graphitization and regulates matrix structure;

[0046] The calcium (Ca) content is 0.5-2.5%, which enhances the deoxidation and desulfurization effects and reduces the surface tension of the molten iron;

[0047] The content of molybdenum (Mo) is 0.2-1.0%, which enhances the high temperature stability of rare earth elements and prolongs the inoculation effect;

[0048] The strontium (Sr) content is 0.1-0.8%, which forms a synergistic deoxidation effect with the scandium-ytterbium-lutetium-terbium rare earth elements;

[0049] Zirconium (Zr) content is 0.1-0.5%, which stabilizes the scandium-ytterbium-lutetium-terbium compound and prevents premature decomposition.

[0050] The addition of auxiliary elements can not only enhance the inoculation effect, but also reduce the amount of rare earth elements and improve economic efficiency. More importantly, there are many complex synergistic mechanisms between auxiliary elements and scandium-ytterbium-lutetium-terbium rare earth elements, such as Mo-Sc-O composite oxide has higher nucleation efficiency than single Sc2O3; Zr-Lu composite compound has better high temperature stability than single Lu compound, etc.

[0051] Carrier element selection:

[0052] Considering the high activity and easy oxidation characteristics of scandium-ytterbium-lutetium-terbium rare earth elements, it is very important to select a suitable carrier element. The present invention selects iron-silicon alloy (Fe-Si) as the basic carrier and adds a small amount of aluminum (Al) to form a protective oxide layer to prevent excessive oxidation of the rare earth elements during preparation and use. The composition of the carrier element is:

[0053] Iron (Fe): balance;

[0054] Aluminum (Al): 0.5-2.0%.

[0055] In order to further improve the effect of the inoculant, the present invention innovatively selects the microscopic morphology of the "core-shell" structure, that is, during the preparation process, a special process is used to enrich the rare earth elements inside the particles to form a "core", while the auxiliary elements are enriched on the surface to form a "shell". This structure is conducive to controlling the release rate of rare earth elements, prolonging the inoculation effect, and reducing the burning loss of rare earth elements.

[0056] Traditional inoculants mainly rely on a single type of nucleation core (such as silicate or oxide) to promote graphite nucleation, while the scandium-ytterbium-lutetium-terbium inoculant of the present invention significantly improves the nucleation efficiency and uniformity by forming multiple types of nucleation cores:

[0057] (1) Sc-OS composite nucleation core: a composite compound formed by scandium, oxygen and sulfur, whose lattice constant is highly matched with graphite (mismatch <3%) and has extremely high nucleation efficiency;

[0058] (2) Yb-Tb oxide nucleation core: The composite oxide formed by ytterbium and terbium has a variable valence state and can dynamically adapt to changes in the molten iron environment;

[0059] (3) Lu-Mo-Zr composite nucleation core: The composite phase formed by lutetium, molybdenum and zirconium has excellent thermal stability and can remain active for a long time in high-temperature molten iron.

[0060] These multi-nucleation cores are evenly distributed in the molten iron, providing a large number of efficient heterogeneous nucleation sites, making graphite nucleation more uniform, smaller and more numerous.

[0061] The variable valence properties of the scandium-ytterbium-lutetium-terbium rare earth elements (especially Yb and Tb) in the present invention enable the inoculant to dynamically adjust the chemical state according to changes in the molten iron environment:

[0062] (1) Temperature-responsive oxygen potential regulation: The valence state of ytterbium changes at different temperatures. At high temperatures, it is mainly +3 valence, with strong deoxidation ability. When the temperature decreases, it partially changes to +2 valence, releasing a small amount of oxygen, creating a suitable trace oxygen environment for graphite nucleation.

[0063] (2) Local redox potential gradient: The +3 / +4 valence state transition of terbium forms a redox potential gradient in the micro-region, which affects the migration and aggregation behavior of carbon atoms;

[0064] (3) Dynamic regulation of sulfur activity: The affinity of the rare earth elements scandium-ytterbium-lutetium-terbium to sulfur changes with temperature, which enables dynamic regulation of sulfur activity, purifying the molten iron without over-desulfurization (over-desulfurization is not conducive to graphite nucleation).

[0065] This dynamic control mechanism enables the inoculant to adapt to different compositions of molten iron and different process conditions, maintaining a stable and efficient inoculation effect.

[0066] The present invention systematically studies the synergistic mechanism of four elements of scandium, ytterbium, lutetium and terbium in cast iron inoculation, and develops a highly efficient cast iron inoculant. The technical scheme and effects of the present invention are described in detail below through multiple embodiments and comparative examples.

[0067] The present invention adopts the following testing method:

[0068] To ensure the reliability and comparability of the results, all examples and comparative examples adopt the following unified testing method:

[0069] 1. Test molten iron: HT250 grey cast iron, basic composition (wt%): C 3.2-3.4, Si 1.8-2.0, Mn 0.5-0.7, P≤0.08, S≤0.06, the rest is Fe.

[0070] 2. Melting process: Use medium frequency induction furnace for melting, melting temperature is 1480±20℃, and furnace temperature is 1420±10℃.

[0071] 3. Inoculation treatment: Add inoculant to molten iron at 1380±10℃, and the pouring temperature is 1350±10℃.

[0072] 4. Sample preparation: Use standard Y-shaped test blocks (GB / T 9441) and Φ30mm cylindrical specimens.

[0073] 5. Tissue observation and quantitative analysis:

[0074] Graphite morphology: observed and analyzed according to GB / T 7216 standard

[0075] Matrix structure: Etched with 4% nitric acid alcohol solution and observed with a metallographic microscope

[0076] Quantitative analysis: Image-Pro Plus image analysis software was used to randomly select 10 fields of view for each sample for statistical analysis.

[0077] 6. Performance testing:

[0078] Tensile strength: Tested according to GB / T 228 standard

[0079] Hardness: Test Brinell hardness according to GB / T 231 standard

[0080] Impact toughness: tested according to GB / T 229 standard

[0081] High temperature performance: tensile strength tested at 300°C, 400°C and 500°C

[0082] Thermal fatigue performance: tested under temperature cycle conditions from 250±10℃ to 650±10℃

[0083] Wear resistance: Tested using MM-200 wear tester in accordance with GB / T 12444 standard

[0084] Incubation decay characteristics: Test performance changes after keeping at 1380±10℃ for 5min, 15min, 30min and 60min

[0085] Example 1: Basic Formula Inoculant

[0086] The composition of the inoculant is, by weight percentage, 1.2% scandium (Sc), 0.8% ytterbium (Yb), 0.4% lutetium (Lu), 0.6% terbium (Tb), 38% silicon (Si), 1.5% calcium (Ca), 0.5% molybdenum (Mo), 0.3% strontium (Sr), 0.3% zirconium (Zr), 1.0% aluminum (Al), and the balance is iron (Fe).

[0087] Preparation process: Iron, silicon, calcium, molybdenum, strontium, zirconium and aluminum are smelted in an induction furnace. After melting, they are kept at 1550±20℃ for 10 minutes to homogenize the alloy. Then scandium, lutetium, terbium and ytterbium are added in turn, kept at 1500±20℃ for 5 minutes, cast into ingots, and crushed into 15-50μm particles after cooling.

[0088] HT250 grey cast iron was inoculated with an addition amount of 0.8%.

[0089] Example 2: High Strength Formula Inoculant

[0090] Composition: Scandium (Sc) 1.8%, ytterbium (Yb) 1.2%, lutetium (Lu) 0.6%, terbium (Tb) 0.9%, silicon (Si) 35%, calcium (Ca) 2.0%, molybdenum (Mo) 0.8%, strontium (Sr) 0.5%, zirconium (Zr) 0.3%, aluminum (Al) 1.5%, and the balance is iron (Fe).

[0091] The preparation process is the same as in Example 1, and the addition amount is 1.0%.

[0092] Example 3: High toughness formula inoculant

[0093] Composition: Scandium (Sc) 0.8%, ytterbium (Yb) 0.5%, lutetium (Lu) 0.25%, terbium (Tb) 0.4%, silicon (Si) 42%, calcium (Ca) 1.0%, molybdenum (Mo) 0.3%, strontium (Sr) 0.2%, zirconium (Zr) 0.2%, aluminum (Al) 0.8%, and the balance is iron (Fe).

[0094] The preparation process is the same as in Example 1, and the addition amount is 0.8%.

[0095] Example 4: High temperature formulation inoculant

[0096] Composition: Scandium (Sc) 1.5%, ytterbium (Yb) 0.6%, lutetium (Lu) 0.7%, terbium (Tb) 0.5%, silicon (Si) 36%, calcium (Ca) 1.2%, molybdenum (Mo) 0.9%, strontium (Sr) 0.3%, zirconium (Zr) 0.4%, aluminum (Al) 1.2%, and the balance is iron (Fe).

[0097] The preparation process is the same as in Example 1, and the addition amount is 0.9%.

[0098] Example 5: Economical Formula Inoculant

[0099] Composition: Scandium (Sc) 0.6%, ytterbium (Yb) 0.4%, lutetium (Lu) 0.2%, terbium (Tb) 0.3%, silicon (Si) 43%, calcium (Ca) 2.2%, molybdenum (Mo) 0.3%, strontium (Sr) 0.6%, zirconium (Zr) 0.2%, aluminum (Al) 0.6%, and the balance is iron (Fe).

[0100] The preparation process is the same as in Example 1, and the addition amount is 0.6%.

[0101] Example 6: High rare earth formula inoculant

[0102] Composition: Scandium (Sc) 2.0%, ytterbium (Yb) 1.3%, lutetium (Lu) 0.7%, terbium (Tb) 1.0%, silicon (Si) 32%, calcium (Ca) 2.5%, molybdenum (Mo) 1.0%, strontium (Sr) 0.8%, zirconium (Zr) 0.5%, aluminum (Al) 2.0%, and the balance is iron (Fe).

[0103] The preparation process is the same as in Example 1, and the addition amount is 1.2%.

[0104] Example 7: Low rare earth formula inoculant

[0105] Composition: Scandium (Sc) 0.5%, ytterbium (Yb) 0.3%, lutetium (Lu) 0.1%, terbium (Tb) 0.2%, silicon (Si) 45%, calcium (Ca) 0.5%, molybdenum (Mo) 0.2%, strontium (Sr) 0.1%, zirconium (Zr) 0.1%, aluminum (Al) 0.5%, and the balance is iron (Fe).

[0106] The preparation process is the same as in Example 1, and the addition amount is 0.5%.

[0107] Example 8: High Scandium-High Terbium Formula Inoculant

[0108] Composition: Scandium (Sc) 1.9%, ytterbium (Yb) 0.5%, lutetium (Lu) 0.3%, terbium (Tb) 0.8%, silicon (Si) 40%, calcium (Ca) 1.8%, molybdenum (Mo) 0.6%, strontium (Sr) 0.4%, zirconium (Zr) 0.3%, aluminum (Al) 1.2%, and the balance is iron (Fe).

[0109] The preparation process is the same as in Example 1, and the addition amount is 0.9%.

[0110] Example 9: High Ytterbium-High Lutetium Formula Inoculant

[0111] Composition: Scandium (Sc) 0.7%, ytterbium (Yb) 1.4%, lutetium (Lu) 0.7%, terbium (Tb) 0.3%, silicon (Si) 37%, calcium (Ca) 1.5%, molybdenum (Mo) 0.7%, strontium (Sr) 0.5%, zirconium (Zr) 0.2%, aluminum (Al) 0.9%, and the balance is iron (Fe).

[0112] The preparation process is the same as in Example 1, and the addition amount is 0.8%.

[0113] Example 10: Balanced Ratio Formula Inoculant

[0114] Composition: Scandium (Sc) 1.0%, Ytterbium (Yb) 0.7%, Lutetium (Lu) 0.3%, Terbium (Tb) 0.5%, Silicon (Si) 40%, Calcium (Ca) 1.5%, Molybdenum (Mo) 0.5%, Strontium (Sr) 0.4%, Zirconium (Zr) 0.3%, Aluminum (Al) 1.0%, and the balance is Iron (Fe).

[0115] The preparation process is the same as in Example 1, and the addition amount is 0.8%.

[0116] Comparative Example 1: Traditional FeSi inoculant

[0117] Composition: Silicon (Si) 75%, aluminum (Al) 1.2%, calcium (Ca) 1.0%, and the balance is iron (Fe).

[0118] The addition amount is 0.8%.

[0119] Comparative Example 2: Traditional rare earth inoculant

[0120] Composition: Silicon (Si) 45%, Cerium (Ce) 1.8%, Lanthanum (La) 0.9%, Calcium (Ca) 2.0%, Aluminum (Al) 1.0%, and the balance is Iron (Fe).

[0121] The addition amount is 0.8%.

[0122] Comparative Example 3: Single Scandium Inoculant

[0123] Composition: Scandium (Sc) 1.2%, Silicon (Si) 40%, Calcium (Ca) 1.5%, Aluminum (Al) 1.0%, and the balance is Iron (Fe).

[0124] The addition amount is 0.8%.

[0125] Comparative Example 4: Single Ytterbium Inoculant

[0126] Composition: ytterbium (Yb) 0.8%, silicon (Si) 40%, calcium (Ca) 1.5%, aluminum (Al) 1.0%, and the balance is iron (Fe).

[0127] The addition amount is 0.8%.

[0128] Comparative Example 5: Single Lutetium Inoculant

[0129] Composition: Lutetium (Lu) 0.4%, Silicon (Si) 40%, Calcium (Ca) 1.5%, Aluminum (Al) 1.0%, and the balance is Iron (Fe).

[0130] The addition amount is 0.8%.

[0131] Comparative Example 6: Single Terbium Inoculant

[0132] Composition: Terbium (Tb) 0.6%, Silicon (Si) 40%, Calcium (Ca) 1.5%, Aluminum (Al) 1.0%, and the balance is Iron (Fe).

[0133] The addition amount is 0.8%.

[0134] Comparative Example 7: Scandium-Ytterbium Combined Inoculant

[0135] Composition: Scandium (Sc) 1.2%, ytterbium (Yb) 0.8%, silicon (Si) 40%, calcium (Ca) 1.5%, aluminum (Al) 1.0%, and the balance is iron (Fe).

[0136] The addition amount is 0.8%.

[0137] Comparative Example 8: Lutetium-Terbium Combination Inoculant

[0138] Composition: Lutetium (Lu) 0.4%, Terbium (Tb) 0.6%, Silicon (Si) 40%, Calcium (Ca) 1.5%, Aluminum (Al) 1.0%, and the balance is Iron (Fe).

[0139] The addition amount is 0.8%.

[0140] Comparative Example 9: Scandium-lutetium-terbium combined inoculant (without ytterbium)

[0141] Composition: Scandium (Sc) 1.2%, Lutetium (Lu) 0.4%, Terbium (Tb) 0.6%, Silicon (Si) 40%, Calcium (Ca) 1.5%, Aluminum (Al) 1.0%, and the balance is Iron (Fe).

[0142] The addition amount is 0.8%.

[0143] Comparative Example 10: Four kinds of rare earth inoculants in equal proportions

[0144] Composition: Scandium (Sc) 0.75%, ytterbium (Yb) 0.75%, lutetium (Lu) 0.75%, terbium (Tb) 0.75%, silicon (Si) 40%, calcium (Ca) 1.5%, aluminum (Al) 1.0%, and the balance is iron (Fe).

[0145] The addition amount is 0.8%.

[0146] The specific experimental results are as follows:

[0147] like Figure 1As shown, there are significant differences between the inoculants of the present invention (Examples 1-10) and the comparative examples (Comparative Examples 1-10) in terms of the proportion of type A graphite, graphite size and graphite quantity. The proportion of type A graphite in the example group is generally higher than 90%, while the conventional 75Si-Fe inoculant (Comparative Example 1) is only 68.5%, and the conventional rare earth inoculant (Comparative Example 2) is 82.3%. In terms of graphite size, the average size of the example group is 35-40μm, which is much smaller than 72.6μm in comparative example 1. In terms of graphite quantity, the example group reaches 350-385 pieces / mm², which is about 2.5 times that of comparative example 1.

[0148] Figure 1 The example groups shown in (a)-(c) have a higher proportion of type A graphite, smaller graphite size and more graphite quantity, indicating that the inoculant of the present invention significantly optimizes the graphite morphology of cast iron.

[0149] Figure 2 The effect of the amount of inoculant added on the graphite morphology in Example 1 is shown. The four curves clearly show that as the addition amount increases from 0.3% to 1.2%, Figure 2 As shown in (a), the proportion of type A graphite increases from 78.5% to 99.2%. Figure 2 (b) shows that the graphite size decreases from 52.3 μm to 30.8 μm. Figure 2 As shown in (c), the number of graphites increases from 215.6 / mm² to 425.3 / mm². Figure 2 As shown in (d), the graphite distribution uniformity increases from 82.5% to 97.5%.

[0150] It is particularly noteworthy that the curve shows obvious nonlinear characteristics. After the addition amount reaches 0.8%, the improvement of various indicators tends to be flat, indicating that 0.8-1.0% is the most economical and effective addition amount range.

[0151] Figure 3 The effects of different inoculants on the matrix structure and their relationship with mechanical properties are shown. Figure 3 (a)-(b) show that the pearlite content of the embodiment group is generally higher than 90%, the ferrite content is lower than 10%, and the average grain size is 18-22 μm, which is significantly better than the comparative example group.

[0152] Figure 3 (c)-(d) Scatter plots reveal the positive correlation between pearlite content and tensile strength and hardness, and the negative correlation between grain size and impact toughness. Example 1 has a pearlite content of 96.5% and a grain size of only 18.3 μm, thus achieving the best combination of mechanical properties. Figure 3 As shown in (d), the impact toughness reaches the optimum value when the grain size is about 20 μm, which is highly consistent with the grain size range produced by the inoculant of the present invention.

[0153] Figure 4 The room temperature and high temperature mechanical properties of different inoculants are comprehensively demonstrated. Figure 4 (a)-(b) compare the tensile strength of each embodiment and the comparative example. The strength of the embodiment group is generally 320-390 MPa, while the comparative example 1 is only 235.6 MPa. The high-strength formula (Example 2 and Example 6) performs particularly well, reaching 386.5 MPa and 390.3 MPa.

[0154] Figure 4 (c)-(d) compare the tensile strength of different samples at room temperature, 300°C, 400°C and 500°C. At a high temperature of 500°C, the embodiment group still maintains a strength of 225-240MPa, while the comparative example 1 is only 135.2MPa. The scatter plot in the lower right shows the correlation between hardness and impact toughness, indicating that the inoculant of the present invention successfully achieves a synergistic improvement in strength and toughness.

[0155] Figure 5 and Figure 6 The analysis focused on high temperature strength retention. Figure 5 The strength retention rates of different samples at a high temperature of 500°C were compared, and the retention rate of the embodiment group reached 61.6-65.5%, which was significantly higher than 57-59% of the comparative group.

[0156] Figure 6 The improvement percentage compared with comparative example 1 is more intuitively shown, with Example 1 and Example 4 improving by 55.8% and 59.7% respectively, showing the significant advantages of the present invention in high-temperature applications. This is of great significance for cast iron parts that need to serve in high-temperature environments.

[0157] Figure 7 The nonlinear relationship between the addition amount and the tensile strength is demonstrated. Figure 7 (a) The strength shows an "S" shape change with the increase of addition amount: it increases rapidly in the range of 0.1-0.8%, tends to be flat in the range of 0.8-1.2%, and decreases slightly after exceeding 1.2%. Figure 7 (b) shows the change in strength growth rate. The growth rate is the highest (18.9%) when the addition amount is 0.3%, and then gradually decreases, and even shows negative growth (-1.2%) at 1.5%.

[0158] This nonlinear relationship proves the existence of an optimal addition amount window (0.8-1.2%) and also reveals the principle that excessive addition is actually disadvantageous, providing important guidance for industrial applications.

[0159] Figure 8 The decay characteristics of different inoculants are shown. Figure 8(a)-(b) compare the effect of holding time on tensile strength and the proportion of type A graphite. After holding for 60 minutes, the tensile strength of Example 1 remains at 325.6 MPa (decay rate 7.6%), while that of Comparative Example 1 decreases to 160.2 MPa (decay rate 38.6%).

[0160] Figure 8 (c)-(d) compare the decay rate changes in detail. The example group (especially Example 4) shows excellent anti-decay performance, and the decay rate after 60 minutes is only 6.8-9.2%, which is much lower than 38.6% of Comparative Example 1 and 22.5% of Comparative Example 2. This long-term and stable inoculation characteristic is extremely important for improving the stability of casting quality.

[0161] Fig. 9 The performance retention characteristics under overheating conditions are demonstrated. Under the extreme condition of molten iron overheating at 150°C, the tensile strength of Example 1 is still maintained at 305.6MPa (retention rate 86.6%), and the proportion of type A graphite is maintained at 82.6%, while the retention rates of Comparative Examples 1 and 2 are only 63.9% and 72.1%, respectively.

[0162] Fig. 9 (c) The gentle slope of the curve indicates that the inoculant of the present invention has excellent adaptability to overheating conditions, which is of great significance for the adaptability to temperature control fluctuations in actual production.

[0163] Fig.10 Thermal fatigue resistance is fully demonstrated. Fig.10 (a)-(b) show that after 1000 thermal cycles, the surface crack density and maximum crack depth of Example 1 are 15.6 lines / cm² and 385.5 μm, respectively, which are only 37% and 45% of those of Comparative Example 1.

[0164] Fig.10 (c) reveals the relationship between grain size and crack growth rate, indicating that the crack growth rate is significantly reduced in the grain size range of 15-30 μm, which is exactly the grain size range (15-20 μm) that can be obtained by the inoculant of the present invention. Fig.10 (d) The comparison shows that Example 4 performs best in terms of thermal fatigue resistance, which is improved by 58.8% compared with Comparative Example 1.

[0165] Fig.11 The wear resistance and its relationship with the microstructure are demonstrated. Fig.11 (a)-(b) compare the mass loss and relative wear resistance under different conditions. The relative wear resistance of Example 1 under dry grinding, oil lubrication and water lubrication conditions reaches 210%, 214% and 220%, respectively, which is much better than the traditional inoculant.

[0166] Fig.11(c)-(d) reveal the relationship between hardness, pearlite content, graphite size and wear resistance. The scatter plot shows that the higher the hardness, the higher the pearlite content, and the smaller the graphite size, the better the wear resistance. Example 2 performs best, with a relative wear resistance of 240%, which corresponds to its highest pearlite content (98.2%) and hardness (285.6HB).

[0167] Fig.12 The synergistic mechanism of scandium-ytterbium-lutetium-terbium elements was demonstrated. Fig.12 (a) shows the effect of a single rare earth element on the proportion of type A graphite, which changes nonlinearly with increasing addition amount. Fig.12 (b) The optimal ratio combination, equal ratio combination and theoretical linear superposition effects were compared. The optimal ratio combination was significantly higher than the linear superposition value, proving the existence of a strong synergistic effect.

[0168] Fig.12 (c) The effects of different combinations on the characteristics of nucleation particles are compared. The four-element optimal ratio combination forms the largest number of nucleation particles with the smallest size. Fig.12 (d) shows that the oxygen activity coefficient and sulfur activity coefficient of the four-element optimal ratio combination are the lowest, indicating that the synergistic purification effect is the best.

[0169] Fig.13 The nucleation efficiency coefficients of different rare earth combinations are shown. As the complexity of the combination increases, the efficiency coefficient increases significantly, from 0.7-1.0 for a single element to 3.5 for the optimal quaternary ratio, indicating a significant synergistic effect.

[0170] Fig.14 The effect of different rare earth combinations on supercooling was analyzed. The supercooling of the quaternary optimal ratio combination was the lowest (12.5°C), which was much lower than the theoretical linear superposition value (18.6°C) and the single element value (22-26°C), indicating that the composite system can significantly improve the nucleation conditions and promote the formation of A-type graphite.

Claims

1. A high-efficiency cast iron inoculant containing rare earth elements, characterized in that: By weight percentage, it includes the following components: Active elements: scandium (Sc) 0.5-2.0%, ytterbium (Yb) 0.3-1.5%, lutetium (Lu) 0.1-0.8%, terbium (Tb) 0.2-1.0%; Auxiliary elements: silicon (Si) 30-45%, calcium (Ca) 0.5-2.5%, molybdenum (Mo) 0.2-1.0%, strontium (Sr) 0.1-0.8%, zirconium (Zr) 0.1-0.5%; Carrier elements: aluminum (Al) 0.5-2.0%, the balance is iron (Fe).

2. The high-efficiency cast iron inoculant containing rare earth elements according to claim 1, characterized in that: The weight ratio of the four rare earth elements scandium, ytterbium, lutetium and terbium is 3:2:1:1.

5.

3. The high-efficiency cast iron inoculant containing rare earth elements according to any one of claims 1-2, characterized in that: The inoculant is used for inoculation treatment of cast iron, and the addition amount is 0.3-1.2%.

Citation Information

Patent Citations

  • High-chromium cast iron composite inoculant, preparation method and application thereof

    CN101580913A

  • Application of strontium-silicon inoculant in silicon-molybdenum spheroidal graphite cast ion

    CN103215487A

  • Nodular cast iron inoculant and preparation method thereof

    CN105950953A

  • Amorphous nucleating agent for CADI cast iron and preparing method and application method of amorphous nucleating agent

    CN106755704A

  • Method for processing molten cast iron

    CN107532225A